2002
DOI: 10.1093/wber/16.1.139
|View full text |Cite
|
Sign up to set email alerts
|

How Different Is the Efficiency of Public and Private Water Companies in Asia?

Abstract: Several studies have compared the efficiency of publicly and privately owned water utilities and reached conflicting conclusions on the impact of ownership on efficiency. This article provides further evidence by estimating a stochastic cost frontier for a sample of Asian and Pacific regional water companies. The results show that efficiency is not significantly different in private companies than in public ones.Policymakers in developing countries, eager to resolve the decade-long debate on the gains from pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
113
3
4

Year Published

2007
2007
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(127 citation statements)
references
References 13 publications
7
113
3
4
Order By: Relevance
“…Inconclusive evidence is also found (Feigembaum and Teeples, 1983;Byrnes et al, 1986;Fox and Hofler, 1986;Jones and Mygind, 2000;Ménard and Saussier, 2000;Estache and Rossi, 2002).…”
Section: Insert Tables 3 4 and 5 About Herementioning
confidence: 88%
See 1 more Smart Citation
“…Inconclusive evidence is also found (Feigembaum and Teeples, 1983;Byrnes et al, 1986;Fox and Hofler, 1986;Jones and Mygind, 2000;Ménard and Saussier, 2000;Estache and Rossi, 2002).…”
Section: Insert Tables 3 4 and 5 About Herementioning
confidence: 88%
“…A number of papers have already introduced this variable to test for its impact on the efficiency of water companies. Although most of them have focused on cost efficiency, their results seem to confirm the existence of economies of density, i.e., the higher the density of population the greater the level of efficiency (Mann and Mikesell, 1976, Teeples and Glyer, 1987, Fabbri and Fraquelli 2000, Antonioli and Filippini, 2001and Estache and Rossi, 2002. Inconclusive evidence is also found by García and Thomas (2001), while Tupper and Resende (2004) find empirical evidence supporting the existence of density economies in the provision of the service of water delivery, but not in the service of sewage collection.…”
Section: Insert Tables 3 4 and 5 About Herementioning
confidence: 99%
“…Using a sample of 50 firms in 19 Asian countries in 1997, Estache and Rossi (2002) Results of empirical studies on the difference of efficiency between public and private water supply are contradictory.…”
Section: Theoretical Issuesmentioning
confidence: 99%
“…10 Whereas several studies conducted in SSA have shown evidence of positive performance trends, most published econometric analyses of the effects of water privatisation in lower-income economies show little evidence that PPPs have resulted in marked improvement in performance. 15,17 Another study carried out in Africa in the late 1990s reported greater service coverage for utilities under PPPs. 18 However, a study of 21 African water utilities conducted in 1995-1997 found that levels of corruption and governance were far more important in explaining difference in efficiency than PPPs.…”
Section: General Utility Performance Under Ppps In Ssamentioning
confidence: 99%
“…18 However, a study of 21 African water utilities conducted in 1995-1997 found that levels of corruption and governance were far more important in explaining difference in efficiency than PPPs. 17 Similarly, findings drawn from analysis of case studies on Guinea, Gabon, Senegal and Cô te d'Ivoire carried out at the turn of the century show that, on the whole, the performance of water utilities under PPPs has not changed dramatically: utilities have continued to perform well or not so well, depending on (a) their state prior to private sector participation (b) factors operating in the external environment.…”
Section: General Utility Performance Under Ppps In Ssamentioning
confidence: 99%